Problems of currency integration - Christian Uhlig (Intereconomics, 1974)
In recent years, the discussion on the forms of organisation of the Franc Zone has again grown more controversial. The present article explains the functional structure of this currency association, and discusses the arguments of its critics.
Keywords: 330; Franc Zone